(untitled) (IMT INTERNATIONAL JOURNAL OF THE ARTS AND SCIENCES, 2024)
The focus of this paper is on the Universal Basic Education (UBE) scheme which is a nine year programme being implemented by the Federal Government of Nigeria, to among other things: eradicate illiteracy, ignorance, reduce the incidence of drop-out-from formal school system; and create the basis for the acquisition of skills and knowledge required for life-long learning. The paper notes that the effective implementation of UBE scheme is bedeviled by myriads of constraints viz: (i) poverty, (ii) lack of commitment by some state governments, (iii) inadequate funding, (iv) ignorance, (v) unqualified teachers, and (vi) inadequate infrastructure. The author has discussed and analysed these constraints and makes some recommendations which when effectively implemented will help in the overall development of the nation. Such implementation is necessary and should be seen as a matter of urgency. This is in view of the fact that basic education is a catalyst for national development.